Distrubution and Morphological Identification of Eel (Anguilla sp.) In Kayoa Sea, South Halmahera, North Maluku - Achmad, M Janib; Akbar, Nebuchadnezzar; Samman, Ardan; Supyan, Supyan; Ismail, Firdaut; Samad, Julkar (Jurnal Kelautan, 2025)
North Maluku Province is an archipelagic province that has a sea area of 113,796.53 km2 or 70% of the land area. As an archipelagic area, North Maluku waters have high biodiversity. One of the important biota in North Maluku waters is the eel. Eel is one of the water resources that have high economic value, because of its nutritional contentEel (Anguilla sp) is a catadromous fish that begins its life in the larval or juvenile phase in marine waters and grows up in brackish and fresh waters. This study aims to determine the distribution of eel species (Anguilla sp) in the seas and the morphometric eel (Anguilla sp) in kayoa waters. The results showed that the number of eels found at both stations was 13 tails. The results of the morphological analysis showed that the type of eel found at both stations was A. marmorata, the morphometric identification results showed that at station 1, the total length range was 50 - 106 cm, with a weight of 460-4100 grams, while at station 2 obtained a length range of 65 cm - 83 cm, with a weight of 79 -1300 grams. Key Word: Area, Morphometri, Anguilla, Small Island, Tropis